(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
Phraseologisms in Turkish, as well as in other languages are used in the integral value, and don’t change the order of the words. For this reason, they can be used in the language instead of a noun, adjective, adverb and verb, and can perform various functions offers. Also phraseologisms have form and semantic features. The article presents a short overview of phraseologisms Turkish language.